A knight without shining armour: the paradox of being a gig worker in Malaysia - Salmie Jemon; Mohd Safri Saiman; Mohammad Puad Bebit; Mohd Ali Hindia (Human Resource Management Academic Research Society (HRMARS), 2021)
Studies on social security in Malaysia can be traced way back to the early years of the 2000s and have become even more dynamically interesting as the world economy is open to new ideas, challenges, and vast potential. The labour market, especially in developing and emerging economies are, prior to the devastative worldwide pandemic of COVID19, entangled with the sad but true impacts of the Industrial Revolution 4.0. Unfortunately, yet interestingly, the former seemed likely to have wider economic impacts and implications for labour-related issues across the globe, not excluding Malaysia. This short article analyses an updated overview of social security in Malaysia as the pandemic goes through a series of oscillating waves of cases experienced by countries worldwide.